Factors Influencing Patient Satisfaction After Decompression Surgery Without Fusion for Lumbar Spinal Stenosis - Ogura, Yoji (Global Spine J, 2019)
STUDY DESIGN: Retrospective cohort study. OBJECTIVES: Decompression without fusion is a standard surgical treatment for lumbar spinal stenosis (LSS) with reasonable surgical outcomes. Nevertheless, some studies have reported low patient satisfaction (PS) following decompression surgery. The cause of the discrepancy between reasonable clinical outcomes and PS is unknown; moreover, the factors associated with PS are expected to be complex, and little is known about them. This study aimed to identify satisfaction rate and to clarify the factors related to PS following decompression surgery in LSS patients. METHODS: We retrospectively reviewed 126 patients who underwent lumbar decompression with a minimum follow-up of 1 year. Patients were divided into 2 groups based on the PS question. The Japanese Orthopaedic Association (JOA) scores, and the Numeric Rating Scale (NRS) scores of low back pain (LBP), leg pain, and leg numbness were compared between the 2 groups preoperatively and at the latest visit. To identify the prognostic factors for dissatisfaction, multiple logistic regression analysis was performed. RESULTS: Overall satisfaction rate was 75%. The JOA recovery rate, NRS improvement, and Short Form–8 (SF-8) were significantly higher in the satisfied group. Postoperative NRS scores of LBP, leg pain, and leg numbness were significantly lower in the satisfied group. Multivariate logistic regression analysis showed that smoking and scoliosis were significant risk factors for dissatisfaction. CONCLUSIONS: Overall satisfaction rate was 75% in patients with LSS undergoing decompression surgery. This study found that smoking status and scoliosis were associated with patient dissatisfaction following decompression in LSS patients.